Determinan Persalinan Prematur di RSUD Dr. Abdul Moeloek - Eliza Eliza; Dina Dwi Nuryani; Rosmiyati Rosmiyati (Jurnal Kesehatan, 2017)
Infant mortality in Indonesia around 56% occurs in the very early period of a neonatal period or newborn. Most of the neonatal deaths occur at the age of 0-6 days (78.5%) and prematurity is the major cause of neonatal death. Based on perinatology room report of Dr. H. Abdul Moeloek hospital in 2015, there were 77 premature births from 391 labors. This number then increased to 84 premature labor from 402 labors by 2016. The objective of this research was to identify the determinants that influenced premature labor in a hospital. H. Abdul Moeloek 2012-2016. This was a quantitative research, design of analytic research was through case control research method. The population was whole pregnant mothers who had premature labor in Dr. H. Abdul Moeloek hospital 2012-2016. The sample was 62 cases and 62 controls to become 138 people. The analysis was through chi-square test. Multivariate analysis used regression logistic. The result showed that there was a significant correlation between mothers’ age (p-value=0,048), parity (p-value=0,000), pregnancy complication (p-value=0,000), KPD (p-value=0,005) and mothers’ education level (p-value = 0,011). The result of the multivariate analysis showed that the most dominant factor towards premature labor was pregnancy complication (p-value=0,000).  The importance of pregnant mothers to make an antenatal care visit in accordance with government program so that abnormalities or complication in pregnancy can be earlier detected.